Global profit shifting, 1975-2019 - Ludvig Wier; Gabriel Zucman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper constructs time series of global profit shifting covering the 2015-19 period, during which major international efforts were implemented to curb profit shifting. We find that (i) multinational profits grew faster than global profits, (ii) the share of multinational profits booked in tax havens remained constant at around 37 per cent, and (iii) the fraction of global corporate tax revenue lost due to profit shifting rose from 9 to 10 per cent. We extend our time series back to 1975 and document a remarkable increase of multinational profits and global profit shifting from 1975 to 2019.
Keywords: H26; E25; F23; 330; multinationals; profit shifting; factor shares; taxation; Gewinnverlagerung; Steueroase; Multinationales Unternehmen; Welt